Intervened URM buildings with RC elements: typological characterisation and associated challenges - Lopes, Gonçalo Correia (2019)
The past reconstruction processes that took place after important earthquakes, and the development and progressive use of reinforced concrete (RC) since the beginning of the twentieth century, led to the creation of a mixed unreinforced masonry–reinforced con‑ crete typology, hereinafter designated as URM–RC. The implementation of such practices, mainly in retroftting interventions of existing unreinforced masonry (URM) buildings, has been spread all over the world, especially due to numerous vague recommendations given in certain building codes. However, over the years, these derived mixed URM–RC buildings revealed to be extremely vulnerable to seismic loads, and their inherent complex structural behaviour is still understudied. Only in recent years researchers have started to turn their attention to the seismic vulnerability of these structures, by studying and observ‑ ing their particular damage patterns, mechanisms and interaction efects from coupling RC structural elements to URM loadbearing walls. Moreover, the benefcial nature of struc‑ tural interventions with RC on URM buildings located in seismically prone regions is still a contentious issue for most of the research community. In this context, the present paper represents a stepping stone for the thorough understanding of the existing derived mixed URM–RC building typologies. A comprehensive cataloguing and categorization of the dif‑ ferent intervention typologies is presented in order to support a more reliable assessment of their seismic vulnerability in future studies, as well as to design proper strengthening inter‑ ventions so as to avoid future disasters. Furthermore, a comprehensive array of open issues is given in a section dedicated to the associated challenges.